THE RELATIONSHIP BETWEEN SOCIAL SUPPORT AND ANXIETY IN FACING THE OBJECTIVE STRUCTURED CLINICAL ASSESSMENT (OSCA) EXAM IN UNDERGRADUATE NURSING STUDENTS - Vina Astuti; Annisa Niken Larasati; Faizal Aulia Ramadhani; Asrofi Noor Mashitoh; Wita Oktaviana; Reja Arrafi (Universitas Kusuma Husada Surakarta, 2025)
Objective Structured Clinical Assessment (OSCA) is one of the evaluation methods used in nursing education to assess students' clinical competence. However, the OSCA exam often causes significant anxiety for nursing students due to high academic and professional demands. Anxiety is a common emotional response experienced by individuals in the face of stressful or challenging situations. One way to reduce anxiety is with good social support. Social support is the opinion of others who tell that individuals need affection, attention, valued, respected, and involved. The purpose of this study was to examine the relationship between social support and the level of anxiety experienced by undergraduate nursing students in facing the OSCA exam. The type of research is quantitative with a cross-sectional approach. The study population was nursing students totalling 572 respondents. This research uses the spearman test, and this research was conducted from August to Septembe. Researchers used non-probability sampling with purposive sampling method, the research sample above showed 90 people to become respondents with inclusion criteria (1. Active students of semester II, IV, IV of the Nursing Study Program at Universitas Muhammadiyah Surakarta who took the OSCA exam, 2. Students take the OSCA exam directly on the appointed day, 3. Willing to fill out the research questionnaire). Measurement of social support using the MSPSS (Multidimensional Scale of Perceived Social Support) questionnaire and the HARS (Hamilton Anxiety Rating Scale) questionnaire for anxiety levels. The results showed that the majority of respondents had moderate social support with 35 respondents (38.9%) and severe anxiety 27 respondents (30%). Data analysis using Spearman Test. Spearmen correlation test results obtained a p-value significance of 0.001 <0.05 and a correlation coefficient value of 0.767. The conclusion of the study is that there is a relationship between social support and anxiety levels in nursing undergraduate students when facing OSCA exams.